A survey of Registered Nurses' educational experiences and self-perceived capability to care for people with intellectual disability and/or autism spectrum disorder. Issue 3 (3rd July 2022) - Cashin, Andrew; Pracilio, Amy; Buckley, Thomas; Kersten, Michelle; Trollor, Julian; Morphet, Julia; Howie, Virginia; Griffin, Ken; Wilson, Nathan J.
ABSTRACT: Aims and Objectives: To survey the educational experience of Registered Nurses in Australia, at undergraduate, post graduate and continuing professional development levels. Background: It has been previously demonstrated that nurses feel unprepared to care for people with intellectually disability and/or autism spectrum disorder in mainstream clinical settings. Specific undergraduate pre-registration curricula content in this domain has been identified to be low in volume, and in the absence of any studies to determine it, it has been presumed that it has diminished over time. Methods: A cross-sectional survey of Australian Registered Nurses using a descriptive survey tool. Results: The level of education undertaken related to intellectual disability and autism spectrum disorder has been consistently low across time and it predates the move from pre-registration hospital based training to the tertiary sector. A relationship was identified between the experience of education and self-reported preparedness, comfort and knowledge to care for people with intellectual disability and/or autism spectrum disorder. Conclusion: Increased educational preparation for nurses to care for people with intellectual disability and/or autism is indicated.